2020
DOI: 10.1542/peds.2020-0242c
|View full text |Cite
|
Sign up to set email alerts
|

Current Research in Pragmatic Language Use Among Deaf and Hard of Hearing Children

Abstract: In this article, we provide a narrative review of research literature on the development of pragmatic skills and the social uses of language in children and adolescents, with a focus on those who are deaf and hard of hearing (DHH). In the review, we consider how pragmatic skills may develop over time for DHH children and adolescents depending on age, language context, amplification devices, and languages and communication modalities. The implications of these findings for enhancing intervention programs for DH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
13
0
2
Order By: Relevance
“…Beyond the effects of parent–child interaction on language development, our model illustrates influences of parent–child interaction on the child’s social communication (pragmatic language), i.e., his/her social use of language, the competence to use language as a means of connecting and engaging with others [ 105 ]. Through a responsive parental interaction style and the adjustment of communication (e.g., strategies to direct attention, visual communication, pacing of interactions) and language complexity to their child’s needs, within natural social situations, the child does not only learn new words and language structures, but learns how to use them effectively in social interactions, e.g., to attract somebody’s attention, to direct somebody’s attention to an object of interest, to express need for help, to share emotions or to ask for the name of an object by pointing at it.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Beyond the effects of parent–child interaction on language development, our model illustrates influences of parent–child interaction on the child’s social communication (pragmatic language), i.e., his/her social use of language, the competence to use language as a means of connecting and engaging with others [ 105 ]. Through a responsive parental interaction style and the adjustment of communication (e.g., strategies to direct attention, visual communication, pacing of interactions) and language complexity to their child’s needs, within natural social situations, the child does not only learn new words and language structures, but learns how to use them effectively in social interactions, e.g., to attract somebody’s attention, to direct somebody’s attention to an object of interest, to express need for help, to share emotions or to ask for the name of an object by pointing at it.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…Even research on children with hearing loss without additional disabilities equally points to the continuing challenge of social communication despite of recent advances in early identification and intervention and resulting improved language outcomes (Paul et al 2020). In a longitudinal study on children with hearing loss Yoshinaga-Itano et al (2020) predicted higher social communication skills by earlier identification and amplification of hearing loss and earlier enrolment in early intervention, lesser degrees of hearing loss, higher nonverbal greater quantity of parent talk and higher parental education.…”
Section: Special Needs Of People With Deafness and Intellectual Disabilitymentioning
confidence: 99%
“…Far beyond the knowledge of formal language (e.g. vocabulary and grammatical skills), SC involves the competence to use language as a "means of connecting and engaging with others" (Paul et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social communication (SC) can be defined as the appropriate use and interpretation of verbal and non-verbal messages within a social context and thus includes much more than the knowledge of language (e.g., vocabulary and grammatical rules). It involves the competence of using language as a “means of connecting and engaging with others” ( 1 ) including three major skills described by the American Speech-Language-Hearing Association ( 2 ). Firstly, SC serves a rich variety of communicative functions of varying degrees of complexity, ranging from attracting somebody's attention to expressing requests and more sophisticated uses of language (e.g., giving hints and using language to persuade others).…”
Section: Introductionmentioning
confidence: 99%
“…Their limited participation in a rich variety of everyday SC situations and the impossibility of overhearing communication between others impacts not only language development, but also the development of SC skills ( 19 ). Despite the recent advances in language development observed in children with pre-lingual deafness due to universal newborn hearing screening, early fitting of hearing aids and/or cochlear implantation, and access to modern family-centered early intervention including the availability of signed language ( 1 ) SC (pragmatic) difficulties are still regarded as a serious challenge in the new generation of children who are DHH with or without an additional ID. Yoshinaga-Itano et al ( 20 ) identified ID as one of the risk factors for SC development in the new generation of children who are DHH.…”
Section: Introductionmentioning
confidence: 99%